On‐line reaction monitoring by mass spectrometry, modern approaches for the analysis of chemical reactions. Issue 4 (19th June 2017) - Ray, Andrew; Bristow, Tony; Whitmore, Chris; Mosely, Jackie
Abstract : The application of on‐line mass spectrometry for direct analysis of chemical and other types of process continues to grow in importance and impact. The ability of the technique to characterize many aspects of a chemical reaction such as product and impurity formation, along with reactant consumption in a single experiment is key to its adoption and development. Innovations in ionization techniques and mass spectrometry instrumentation are enabling this adoption. An increasing range of ambient ionization techniques make on‐line mass spectrometry applicable to a large range of chemistries. The academic development and commercialization of small footprint portable/transportable mass spectrometers is providing technology that can be positioned with any process under investigation. These developments, coupled with research into new ways of sampling representatively from both the condensed and gaseous phases, are positioning mass spectrometry as an essential technology for on‐line process optimization, understanding and intelligent control. It is recognized that quantitative capability of mass spectrometry in this application can cause some resistance to its adoption, but research activities to tackle this limitation are on‐going.